Front Cover: CuTiPS5 – A New Structure Type with a Corrugated Layered Network Structure (Z. Anorg. Allg. Chem. 23/2017). Issue 23 (5th December 2017) - Dressel, Carina B.; Klein, Wilhelm; Fässler, Thomas F.
Abstract : The Front Cover shows two forms of wavy patterns involving the element titanium. Whereas the architect Frank Gehry frequently applies titanium cladding to cover the wavy surface of buildings, reveals the structure of CuTiPS5 corrugated layers by an unique connection of TiS6 octahedra and CuS4 as well as PS4 tetrahedra. Synthesis and structure of this novel sulfide that contains structure details of both TiS2 and Cu3 PS4 are discussed in the article by Thomas F. Fässler et al. on page1814 ff . The Front cover was designed by Dominique Marchand Fässler.